2021
DOI: 10.3390/ph14111181
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics in Intestinal Mucosal Healing: A New Therapy or an Old Friend?

Abstract: Inflammatory bowel disease (IBD), Crohn’s disease, and ulcerative colitis are characterized by chronic and relapsing inflammation, while their pathogenesis remains mostly unelucidated. Gut commensal microbiota seem to be one of the various implicated factors, as several studies have shown a significant decrease in the microbiome diversity of patients with IBD. Although the question of whether microbiota dysbiosis is a causal factor or the result of chronic inflammation remains unanswered, one fact is clear; ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 158 publications
0
8
0
Order By: Relevance
“…Similarly, the probiotic products Symprove and VSL#3, also can regulate microbial dysbiosis and restore barrier function in UC patients ( Ghyselinck et al, 2020 ). Some experts believe that probiotics should be considered not only a simple dietary supplement, but also a potential therapeutic factor for UC ( Filidou and Kolios, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the probiotic products Symprove and VSL#3, also can regulate microbial dysbiosis and restore barrier function in UC patients ( Ghyselinck et al, 2020 ). Some experts believe that probiotics should be considered not only a simple dietary supplement, but also a potential therapeutic factor for UC ( Filidou and Kolios, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the transfer of living microorganisms, mostly Lactobacillus phyla, has exerted benefical effects on mucosal healing in murine models of DSS-colitis and gastric ulcera (62).…”
Section: Future Aspectsmentioning
confidence: 99%
“…9 In IBD, the significant increase in the number of pathogens within the intestines and the decrease in beneficial bacteria substantially dictate the alterations in the structure and function of the ISC niche 6,15 microbial metabolism is, therefore, a promising therapy for regulating the ISC functions. 16 Recent advances underscore the significant roles of probiotics and prebiotics in the healing of intestinal mucosa barrier, 17 particularly in regulating ISCs. Key studies have illuminated these roles: Lee et al demonstrated that lactic acid bacteria (LAB) enhance ISCs, Paneth, and goblet cell proliferation via lactate-stimulated Wnt/β-catenin signaling.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent advances underscore the significant roles of probiotics and prebiotics in the healing of intestinal mucosa barrier, particularly in regulating ISCs. Key studies have illuminated these roles: Lee et al demonstrated that lactic acid bacteria (LAB) enhance ISCs, Paneth, and goblet cell proliferation via lactate-stimulated Wnt/β-catenin signaling .…”
Section: Introductionmentioning
confidence: 99%